The Oxford handbook of lexicography - Durkin, Philip (Oxford University Press, 2016)
Providing authoritative accounts of the approaches and methodologies of modern lexicography and of the aims of its end products, this book brings together leading scholars and professional lexicographers from all over the world and representing all the main traditions and perspectives.
Keywords: Aufsatzsammlung; Lexikografie